Analisis Tingkat Ketertarikan Siswa Kelas V terhadap Pembelajaran Bahasa Indonesia di SD Singosari - Cindy Cantika br Tarigan; Yulika Aghnesia Manik; Tohap Panuturi Sihombing; Riandita Kd. Pasaribu; Roseska Natalia Marito Simanjuntak (Jurnal Keluarga Sehat Sejahtera, 2026)
This study aims to analyze the level of students’ interest in learning Indonesian language at Singosari Elementary School. Students’ interest in the learning process is one of the important factors that influences motivation, participation, and learning outcomes. This research used a quantitative approach with a survey method. The research instrument was a questionnaire developed based on indicators of learning interest, including students’ attention, enjoyment, participation in learning activities, and motivation to attend Indonesian language lessons. The subjects of this study were sixth-grade students of Singosari Elementary School. The collected data were analyzed using descriptive statistical techniques to determine the level of students’ interest in learning Indonesian language. The results showed that most students had a moderate to high level of interest. Factors influencing students’ interest included the teaching methods used by the teacher, attractive learning media, and active interaction between teachers and students during the learning process. Therefore, Indonesian language learning at Singosari Elementary School has been able to attract students’ interest, although innovation in learning strategies is still needed to further improve students’ interest in learning.